2019
DOI: 10.1080/09654313.2019.1606897
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration, foreign firms and firm exit in regions under transition: the increasing importance of related variety in Hungary

Abstract: Related variety of economic activities is widely recognized to induce regional development; however, it is not clear how this mechanism takes place in regions that go through major structural and institutional transformation. Furthermore, foreign direct investment (FDI) is typically a major source of structural change in these areas; and we still need a better understanding on how foreign-owned (foreign) firms affect the dynamics of domestic-owned (domestic) companies. For these reasons we analyse firm-level e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 76 publications
0
13
0
1
Order By: Relevance
“…Similar topics have also been investigated, e.g., from the perspective of a foreign shareholder's involvement in local business structure in various regions, including e. g. Italy (Gamba & Montanaro, 2009or Bentivogli & Mirenda, 2017, Norway (Ivanova et al, 2019), Poland (Nazarczuk & Krajewska, 2018), or Hungary (Kanó et al, 2019). Concerning the two latter countries, Elekes et al (2019) showed in a study of 67 Hungarian regions that foreign firms induce more structural change in regions than domestic firms do, and above-mentioned Nazarczuk and Krajewska (2018) proved that urbanisation was a significant factor describing the spatial agglomeration of FDIs in Poland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar topics have also been investigated, e.g., from the perspective of a foreign shareholder's involvement in local business structure in various regions, including e. g. Italy (Gamba & Montanaro, 2009or Bentivogli & Mirenda, 2017, Norway (Ivanova et al, 2019), Poland (Nazarczuk & Krajewska, 2018), or Hungary (Kanó et al, 2019). Concerning the two latter countries, Elekes et al (2019) showed in a study of 67 Hungarian regions that foreign firms induce more structural change in regions than domestic firms do, and above-mentioned Nazarczuk and Krajewska (2018) proved that urbanisation was a significant factor describing the spatial agglomeration of FDIs in Poland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is demonstrated that economic diversification is closely related to the current production structures; therefore, the recovery of the economy through sectoral related diversification should be approached in conjunction with other major processes, among which deindustrialization, skillbiased technological change, job polarization, and urbanization to influence the regional growth, requesting an increased role for policy and entrepreneurship to support unrelated diversification (Holm & Østergaard, 2018). Consequently, there are many structural barriers to economic development, especially in CEE regions having to cope with fast and profound institutional changes and inherited industrial structures (Szakálné Kanó et al, 2019).…”
Section: Deindustrialization In the 1990smentioning
confidence: 99%
“…There is wide recognition of the role direct foreign investments play in the post-1990 development of CEE countries in terms of economic growth, productivity improvement, and integration in the global supply chains. The bright side of international investment inflows is highlighted by the formative role of FDI in transition economies where domestic firms benefit from being agglomerated with technologically related foreign firms (Szakálné Kanó et al, 2019). The knowledge and technology transfer is central to the modernization of regional economies, especially because, as Boschma and Capone (2016) maintain, Eastern European countries, as compared with Western European ones, tend to diversify into new industries that are more closely related to their existing industries.…”
Section: Exogenously-led Growth Of Manufacturingmentioning
confidence: 99%
“…Finally, we adapt the related cluster variety to only consider either the presence of domestic or multinational industries in a region. We follow the same approach as Szakálné Kanó et al (2019). Considering only domestic industries in region r and at time t, p d (i, r, t) = 1/n d .…”
Section: Defining Our Cohesion Measuresmentioning
confidence: 99%
“…To detect these relationships we set up a panel probit regression model in a similar frame to Neffke et al (2011a) andSzakálné Kanó et al (2019).…”
Section: Modelling Frameworkmentioning
confidence: 99%